Development of an Empirical Bulk Modulus Model of Ternary Chalcopyrite Structure Solids - S. K. Gorai (Research Trends and Challenges in Physical Science Vol. 5, 2021)
A simple empirical relationship has been proposed to estimate the bulk modulus (B) of ternary chalcopyrite structure solids of I-II-VI, II-IV-V type from the electronegativities of the constituent atoms and the principal quantum number of the compounds. The current relationship is based on a model of chemical bonding. The chemical bonding of constituent atoms of compounds is determined by electronegativity and principal quantum number. Chemical bonding is the beginning point for a compound’s stability, which is based on the minimal energy principle. The nature of material bonding was correlated with ground state properties such as bulk modulus in this study. The bonding of ternary chalcopyrite structure solids is well explained by the combination of electronegativity and main quantum number. These two metrics are a good indicator of chalcopyrite structure solids’ structural stability. The computed bulk modulus values are found to be in good agreement with known values, and a comparison of our current results to those in the literature is also provided. In the present study, it is found that electronegativity and average principal quantum number which expresses the nature of bonding in chalcopyrites.